Zoning Desertification Risks by using ICD and MICD models in Niatak Region of Sistan, Iran - Hosseini, S M; Feyzolahpour, M; Sadrafshari, S; Hashemi, M (Annals of Arid Zone, 2019)
Desertification phenomenon threatens a considerable portion of the world andis developing rapidly. This has occurred more acutely in Iran. Thus, in this research,the current conditions, type and intensity of factors influencing desertification of NiatakRegion of Sistan were investigated by using Iranian Classification of Desertification(ICD) and Modified Iranian Classification of Desertification (MICD). In ICD model,scores were given to the six influential factors in desertification of each working unit.Based on the results obtained from ICD model, the study area was divided into threeclasses (medium, high and very high) according to their desertification intensities. Themedium, high, and very high classes were about 2857.42, 1503.17 and 459.1 hectares,respectively. However, based on the results obtained from MICD model, the medium,high and very high classes desertification covers an area of about 1974.84 hectares (41%),2385.71 hectares (49.5%) and 459.1 hectares 9.5% of the entire region, respectively.Key words: Desertification, wind erosion, scoring, ICD, MICD, Niatak of Sistan.